2014
DOI: 10.1380/ejssnt.2014.242
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Novel Electromagnetic Shielding Sheets Using Carbon-Nanotube-Composite Paper

Abstract: We propose a new electromagnetic shielding (EMS) sheet that uses carbon nanotube (CNT)-composite paper. The electromagnetic environment in which electronic devices such as mobile phones and personal computers operate has become increasingly complex due to increased electromagnetic noise. This noise can cause unexpected behavior in electronic devices. Therefore, EMS sheets are required to shield devices from this noise. Carbon-nanotube composite paper has high electrical conductivity despite being a paper and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Conductive polymer composites containing conductive nanostructured fillers (metallic particles, metallic and carbon fibers, blacks, etc.) reach such technical level, which make them competitive with conventional conductive materials (metals) due to low manufacturing cost, low density, manufacturability (compatibility and possibility to produce elements of arbitrary shape), corrosion resistance and ecological safety 8 . Recently it was showed that using nanostructural elements assembled at different length scales within the binding matrix could result in tunable dielectric response over a wide frequency range 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymer composites containing conductive nanostructured fillers (metallic particles, metallic and carbon fibers, blacks, etc.) reach such technical level, which make them competitive with conventional conductive materials (metals) due to low manufacturing cost, low density, manufacturability (compatibility and possibility to produce elements of arbitrary shape), corrosion resistance and ecological safety 8 . Recently it was showed that using nanostructural elements assembled at different length scales within the binding matrix could result in tunable dielectric response over a wide frequency range 9 .…”
Section: Introductionmentioning
confidence: 99%
“…where S 0 is the cross-section area per one atom of the lattice and Γ is the measure of the scattering strength. It was suggested in [15] that grain boundaries can be naturally described by disclinations. In graphene, the alternating pentagon-heptagon structure along high-angle GBs was revealed in [8].…”
mentioning
confidence: 99%
“…A previous study demonstrated a cellulose/CNT composite paper with high EM shielding performance. 27,28) This composite paper showed a high conductivity of 1.9 × 10 2 S m −1 with 8.3 wt% CNTs and a high shielding performance of 20-40 dB in the range of 15-40 GHz. 27) However, the density of these CNT composite papers was approximately 1.2 × 10 3 mg cm −3 .…”
Section: Resultsmentioning
confidence: 96%